Organo-Mineral Fertilization Based on Olive Waste Sludge Compost and Various Phosphate Sources Improves Phosphorus Agronomic Efficiency, Zea mays Agro-Physiological Traits, and Water Availability - Youness Bouhia; Mohamed Hafidi; Yedir Ouhdouch; Youssef Zeroual; Karim Lyamlouli (Agronomy, 2023)
In the context of intensive and sustainable agriculture, limiting soil degradation and the loss of organic matter has become an obligation to maintain food security. The use of organo-mineral fertilizer (OMF) products is an innovative technology that may solve the different challenges raised. This study aimed to evaluate the effect of various organo-mineral fertilizer (OMF) formulations on Zea mays agro-physiological traits, phosphorus (P)-related parameters, and water conservation during a 90-day pot experiment. The OMF formulations consisted of blending several doses of a stable OMWS compost (10 t /ha(OMF1), 50 t/ha (OMF2), or 100 t/ha (OMF3)) with different sources of mineral P, namely diammonium phosphate (DAP), rock phosphate (RP), or phosphate washing sludge (PWS), compared with separate applications. The results indicated that the effect of an OMF on the soil and plants was strongly dependent on the source of P used and the dose of OMWS compost. The best agronomic performance was attributed to OMF1-based DAP, which resulted in a significant improvement in the shoot and root biomass dry weight by more than 260% and 40%, respectively. However, using an OMF2 formulation was more optimal when using RP and PWS as mineral P sources. Independently of the type of P fertilizer, the addition of stable OM systematically improved multiple soil properties, including water availability, and the nutrient concentrations, such as the available P, exchangeable potassium, and magnesium. Furthermore, the plant’s respiration, photosynthetic activity, and nutrient assimilations were positively affected by the OMF formulations. Overall, our results demonstrate that organo-mineral fertilization is a promising solution for increasing the efficiency of low-P and high-P mineral fertilizers in alkaline soils through direct and indirect mechanisms involving improved soil properties and higher P solubilization.